Acute effects of Amomum villosum Lour. fruit extract on postprandial glycemia and insulin secretion: A single-blind, placebo-controlled, crossover study in healthy subjects - Kim, Ha-Rim; Paulrayer, Antonisamy; Kwon, Yong-Gwan; Ryu, Do-Gon; Baek, Dong-Gi; Geum, Ji-Hye; Lee, Jung-Han; Lee, Geum-San; Kwon, Kang-Beom (Saudi journal of biological sciences, 2020)
Lour., (Zingiberaceae) an herbaceous plant in the ginger family, has been used to treat various diseases. In a single-blind, randomized, crossover study, we assessed the postprandial blood insulin and blood glucose responses in healthy subjects (n = 40) after the water extract (AVE) (5 g/person) or a placebo (5 g/person) consumption. During each treatment course, the healthy subject consumed a regular late afternoon meal, followed by fasting for 12 h, and arrived at the clinical study center the next morning. Blood insulin and blood glucose levels were assessed at 0, 30, 60, 90, and 120 min after AVE consumption. Between each treatment, the subjects accomplished one week of a washout period. The AVE intake demonstrated a significant (67.26%) decline in postprandial blood glucose AUC (incremental area under the curve from 0 to 120 min) versus the placebo ( = 0.011). Furthermore, AVE reduced postprandial blood insulin AUC by 59.95% compared to the placebo group ( < 0.003), supporting the blood glucose results. This study revealed that AVE consumption significantly reduced postprandial insulin and glucose levels in healthy individuals, due in part to inhibition of α-glucosidase, and glucose transport.